2016
DOI: 10.1590/s1806-92902016001100001
|View full text |Cite
|
Sign up to set email alerts
|

Usability of CART algorithm for determining egg quality characteristics influencing fertility in the eggs of Japanese quail

Abstract: -The objective of this study was to determine the effects of egg quality characteristics (egg weight, egg width, egg height, and shape index) on fertility of eggs of Japanese quail with different colored feathers (yellow, white, grizzled, and normal), which are of economic importance for poultry production. For this purpose, 383 eggs of Japanese quail with various feather colors were used. In the study, usability of classification and regression tree (CART) data-mining algorithm as a classification tree method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The root node is the sample to be divided in the entire microarray dataset, where each gene is the attribute to be selected. And the bifurcation node of the tree is a selected attribute value, and the leaf nodes of the tree represent the class to which the tester belongs [ 9 ]. The growth process of the decision tree is the construction process of the classifier.…”
Section: Decision Tree Algorithm and Laparoscopic Image Technologymentioning
confidence: 99%
“…The root node is the sample to be divided in the entire microarray dataset, where each gene is the attribute to be selected. And the bifurcation node of the tree is a selected attribute value, and the leaf nodes of the tree represent the class to which the tester belongs [ 9 ]. The growth process of the decision tree is the construction process of the classifier.…”
Section: Decision Tree Algorithm and Laparoscopic Image Technologymentioning
confidence: 99%
“…Such method was applied by Çelik et al. (2016), who were looking for Japanese quail egg traits that combine with high fertility rate. Using the CART (classification and regression tree) algorithm, they showed that the highest fertility ratio—90.9% is achieved for eggs of very specific quails.…”
Section: Introductionmentioning
confidence: 99%